Tradisi Pakaian Baru pada Hari Raya di Madura: Studi Living Hadith - Zamzami, Mohammad Subhan (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2020)
Abstract: The living tradition of new outfit on the feast day in Madura which passes down through generations has been considered only as a local tradition, whereas it is basically rooted from the hadith and the practices of the prophet’s companions. This article attempts to discuss the hadith on the tradition of the new outfit on the feast day, the Madurese’s view of this tradition, and the identification and urgency of this tradition as a living hadith. Based on the theory of acculturation and living hadith, this article concludes that: (a) The hadith about this tradition was narrated by al-Bukhārī, Muslim, and al-Nasā’ī; (b) The Madurese’s views on this tradition are varied, even contradictory depending on their perspectives and experiences; and (c) This tradition belongs to a living hadith on its material aspects for its existence seems to be rooted from the hadiths and the practices of the prophet’s companions. It reflects elements of obedience, respect, expressions of happiness, compassion, preservation of Islamic tradition, and differentiation between one moment from another. Keywords: Living hadith; new outfit; the feast day; Madura. Abstrak: Tradisi pakaian baru pada hari raya di Madura merupakan tradisi yang diwariskan lintas generasi yang dianggap hanya sebagai tradisi lokal. Padahal ia berasal dari hadis dan praktik sahabat. Artikel ini mendiskusikan secara deskriptif-analitis hadis tentang tradisi pakaian baru pada hari raya, pandangan masyarakat Madura tentang tradisi ini, identifikasi dan urgensi tradisi ini di Madura sebagai living hadith. Berdasarkan teori akulturasi dan living hadith, artikel ini menyimpulkan bahwa: (a) Hadis tentang tradisi ini diriwayatkan al-Bukhārī, Muslim, dan al-Nasā’ī; (b) Pandangan orang Madura tentang tradisi ini beragam, bahkan kontradiktif tergantung pada perspektif dan pengalamannya; dan (c) Tradisi ini merupakan living hadith kebendaan pada aspek matan, karena keberadaannya diilhami oleh hadis dan praktik sahabat. Ia mengandung unsur kepatuhan, penghormatan, ekspresi kebahagiaan, kasih sayang, pelestarian tradisi Islam, dan pembedaan antara suatu momentum dari momentum lain. Kata Kunci: Tradisi, pakaian baru, living hadith, hari raya, Madura.